PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD BERBANTUAN MEDIA LEAFLET DILENGKAPI QUESTION BOX UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS VII - Naha Ana Awa, Rambu; Makaborang, Yohana; Rosalia Ndapa Huda, Marleni (Jurnal Biogenerasi, 2025)
This study aims to improve the learning outcomes of students of class VIIA SMP Negeri 2 Pahunga Lodu on the material of the Earth and Solar System through a cooperative learning model of Student Teams Achievement Division (STAD) type assisted by leaflet and question box media. The type of research applied is Classroom Action Research (PTK) with the Kemmis and Mc. Taggart model. The research subjects of class VIIA amounted to 33 students. The results showed an increase in the average cognitive score from 48.18 in the pre-cycle to 66.96 in cycle II, while learning completeness from 30.30% to 81.81% in cycle II. In the affective aspect, there was also an increase, with a very high category reaching 75.75% in cycle II. With the above percentage results, the application of the STAD type cooperative learning model assisted by leaflet media equipped with question boxes is proven effective in improving student learning outcomes.